2018
DOI: 10.1002/ceat.201800063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Process Parameters on an Inverse Concentrated Miniemulsion Flowing in a Microchannel

Abstract: Emulsions are of great industrial interest due to their wide variety and end‐use properties. Microfluidics systems provide excellent control of transport phenomena. Hence, the influence of operating parameters on a concentrated inverse miniemulsion flowing in a microfluidic system was investigated. The feasibility of maintaining the emulsion in a microfluidic device was clearly demonstrated and the associated operating domain identified. Due to its influence on rheology, the effect of temperature on the drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Studies in this area have revealed that the microchannel technology has a diverse spectrum of applications, because of its superior heat- and mass-transfer features, as well as its small size . Applications described in various studies include solvent extraction, emulsification, , polymerization, , and chemical and biomedical synthesis. , Although the process is viewed as being more efficient, unlike the gas–liquid systems, the studies available in the open literature are still limited in number, because of the difficulty in achieving a stable pattern in the two immiscible liquids flow in a microchannel. Thus, in order to design and control an efficient and practical system, it is vital to understand the flow behavior in the two-phase systems in general, , and much of this work remains to be done.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this area have revealed that the microchannel technology has a diverse spectrum of applications, because of its superior heat- and mass-transfer features, as well as its small size . Applications described in various studies include solvent extraction, emulsification, , polymerization, , and chemical and biomedical synthesis. , Although the process is viewed as being more efficient, unlike the gas–liquid systems, the studies available in the open literature are still limited in number, because of the difficulty in achieving a stable pattern in the two immiscible liquids flow in a microchannel. Thus, in order to design and control an efficient and practical system, it is vital to understand the flow behavior in the two-phase systems in general, , and much of this work remains to be done.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in numbering up microfluidic devices to achieve a throughput of more than 1 kg h −1 , many microfluidic approaches require complex mixer geometries and fabrication methods with micron tolerances . Temperature variation can also have an effect on the emulsion dimensions, but the effect is limited . Placing a wire inside an available X‐mixer provides a cost‐efficient yet powerful method to improve the droplet uniformity and gain control over the droplet size.…”
Section: Introductionmentioning
confidence: 99%